Dinamisme Islam dalam Perspektif Muhammad Iqbal: Ide Pembaharuan di Anak Benua India - Zulkifli Reza Fahmi Fahmi (Sekolah Tinggi Agama Islam AL Aqidah Al Hasyimiyyah Jakarta, 2024)
Entering the modern era marked by advancements in science and technology, especially after the opening of the 19th century, Islam faced contact with the Western world, which subsequently brought new ideas into the Islamic world. This created new issues in the Islamic world, which prompted Islamic intellectuals to respond to these developments. At the same time, the Islamic world was facing a stage of stagnation and static, where the Muslim community was bound by all the results of the classic scholars' ijtihad. Iqbal's presence among the Muslim community on the Indian subcontinent aims to bring the Muslim community out of stagnation towards a more dynamic and progressive Islam. The author used a qualitative descriptive research method. The research type is a library research - a literature-based research with data taken from written materials, such as books or others that are related to the discussion topic. The results of the research found that Sir Muhammad Iqbal was one of the Muslim reform figures in India who encouraged dynamism in Islam. He saw that the main factor that caused the Muslim community to become stagnant, static, and rigid was the closed door of ijtihad. He believed that the values of the Qur'an essentially awaken humans to a higher awareness of their relationship with God and the universe. The Qur'an does not cover this detail, but humans are demanded to be creative and innovative in responding to it and create changes. In the terminology of fiqh, this is called ijtihad and, in Iqbal's view, is called the principle of movement in the structure of Islam.